Flowering time and pollinator abundance determine the female reproductive success in the dioecious palm Chamaedorea pinnatifrons (Arecaceae) - Cascante-Marín, Alfredo; Barrantes, Gilbert; Ríos, Luis D.; Fuchs, Eric J. (Revista de Biología Tropical, 2025)
Introduction: Female fecundity in dioecious plants is influenced by ecological factors that affect pollen and pollinator availability. A high flowering synchrony between sexes, an abundance of pollen donors and pollinators are expected to increase female reproductive success. Objective: To understand how fruit production is related to flowering phenology, sex ratio, abundance and proximity of reproductive males to focal pistillate plants, and pollinator abundance in the dioecious understory palm Chamaedorea pinnatifrons (Arecaceae). Methods: We followed the population flowering of the study species in a montane forest in Costa Rica during 2012. We correlated the number of fruits and fruit set from 115 inflorescences (74 plants) with the size of male and female neighborhoods surrounding focal plants, as well as with plant size and floral display (number of flowers per inflorescence). We estimated pollinator abundance by sampling thrips (Thysanoptera) from staminate inflorescences throughout the plant reproductive season. Results: Flowering was seasonal, with a high degree of overlap between the sexes. The sex ratio of reproductive plants did not significantly deviate from one (79 females and 88 males). Female reproductive success was not related to the abundance and proximity of pollen donors but was instead associated with plants possessing shorter stems, more leaves and flowers per inflorescence, and fewer female neighbors. Late-flowering inflorescences significantly produced more fruits and had a higher fruit set, which coincided with an increase in thrips abundance. Conclusions: We hypothesized that a higher floral display acts as a signal effect to attract pollinators, while larger inflorescences with more flowers can attract more insects, resulting in greater pollination success. Moreover, late-flowering inflorescences seem to benefit from the increase in pollinator abundance at the end of the flowering season. Pollination of C. pinnatifrons and other Chamaedorea species is highly dependent on thrips; as a result, the reproductive success of these palms is susceptible to fluctuations in pollinator population sizes.